Amélioration de L’efficacité Énergétique par L’intégration de Systèmes Solaires sur les Parois Verticales des Locaux: Expérimentation sur Site - Sobhi, Fatma; Chebboub, Imane; Bouchekima, Bachir (ورقلة, 2019)
In this study, we present the results of an experimental work on the integration of an air solar collector at the facade of a house. We manufactured a single solar collector and another with baffles. Firstly, the method of producing the experimental prototype is described with reference to the standard air sensor models, then a measurement campaign is run to judge the thermal performance of this system. The results show that the solar collector with the baffles gives a higher yield than the single solar collector. The measured parameters allowed us to support the theoretical analysis, to valorize the solar air collector for a possible use in the heating of the buildings within the framework of the improvement of the thermal comfort.
Keywords: الطاقة الشمسية -- المجمع الشمسي -- الراحة الحرارية -- الجزائر